Molluscicidal activity in front of the Biomphalaria glabrata snail of the essential oil of Origanum vulgare L. (Research, Society and Development, 2021)
This study evaluated the molluscicidal activity in front of the snail transmitting the schistosomes (Biomphalaria glabrata) of the essential oil of Origanum vulgare. The plant material was collected in the municipality of São Luis (MA). The essential oil was extracted by hydrodistillation at 100° C for 3h, with chemical characterization through Gas Chromatography coupled to Mass Spectrometry (GC-MS). For molluscicidal activity, the methodology recommended by the WHO was performed, and the LC50 of the essential oil was used in the face of the snail obtained by the Probit method. The major constituents found in the essential oil of O. vulgare were Timol (72,14%) and p-cimene (12,25%). A atividade moluscicida do óleo essencial apresentou a CL50 de 26,55 mg L-1. The results indicate that the evaluated essential oil is composed of substances that promote and encourage its application, due to its high potential for molluscicidal activity against Biomphalaria glabrata.